Implementation of Public Service Principles at Sabak Auh Sub-district Head Office in Siak Regency - Nuraisah Nuraisah; Lilis Wahyuni (Universitas Medan Area, 2020)
This article aims to find out the implementation of the principles of public service at the Sabak Auh District Office of Siak Regency. Data were collected through observation interviews and documentation and analyzed qualitatively. The result of this study concludes that the implementation of the principles of public service at Sabak Auh Sub-District Office Siak Regency was not yet fully good there were still some weaknesses in supporting the implementation of the principles of public service at Sabak Auh Sub-district Office in Siak Regency. To implement the principles of public service at Sabak Auh Sub-District Office, Siak Regency it was guided by the vision and mission of administrative services so that public satisfaction with public services increases and the image of the Sabak Auh Sub-District Office was recognized by the community.